Atractylenolide I Ameliorates Acetaminophen-Induced Acute Liver Injury via the TLR4/MAPKs/NF-κB Signaling Pathways - Du, Zhongyan; Ma, Zhimei; Lai, Shanglei; Ding, Qinchao; Hu, Ziyi; Yang, Wenwen; Qian, Qianyu; Zhu, Linwensi; Dou, Xiaobing; Li, Songtao (Frontiers in Pharmacology, 2022)
Background: Acetaminophen (APAP) overdose results in the production of reactive oxygen species (ROS), induces hepatocyte necrosis, and leads to acute liver failure. Atractylenolide I (AO-I), a phytochemical found in Atractylodes macrocephala Koidz, is known to exhibit antioxidant activity. However, its clinical benefits against drug-induced liver injury remain largely unclear. Purpose: This study aimed at evaluating the protective effects of AO-I against APAP-induced acute liver injury. Methods: C57BL/6 mice were administered 500 mg/kg APAP to induce hepatotoxicity. AO-Ⅰ (60 and 120 mg/kg) was intragastrically administered 2 h before APAP dosing. Liver histopathological changes, oxidative stress and hepatic inflammation markers from each group were observed. Resluts: We observed that AO-I treatment significantly reversed APAP-induced liver injury, as evidenced by improved plasma alanine transaminase (ALT) level, aspartate aminotransferase (AST) and liver H&E stain. APAP treatment increased liver malondialdehyde (MDA) content and reduced catalase (CAT) and glutathione (GSH) level; however, these effects were alleviated by AO-I intervention. Moreover, AO-I treatment significantly inhibited APAP-induced activation of pro-inflammatory factors, such as IL-1β, IL-6, and TNF-α, at both the mRNA and protein levels. Mechanistic studies revealed that AO-I attenuated APAP-induced activation of TLR4, NF-κB and MAPKs (including JNK and p38). Conclusion: AO-I mediates protective effects against APAP-induced hepatotoxicity via the TLR4/MAPKs/NF-κB pathways. Thus, AO-I is a candidate therapeutic compound for APAP-induced hepatotoxicity.